Nano structure Ti-doped skutterudite CoSb3 thin films through layer inter-diffusion for enhanced thermoelectric properties. Issue 15 (December 2019) - Liang, Guang-xing; Zheng, Zhuang-hao; Li, Fu; Luo, Jing-ting; Jin, Hao; Zhang, Xiang-hua; Fan, Ping
Abstract: Ti-doped CoSb3 thin films were prepared through layer inter-diffusion method and the prepared thin films have unique architecture, containing nano-size grains. According to the Raman analysis, the films have weaker atomic vibration after Ti doping. This nano-structure and the weak atomic vibration can scatter a wide-range spectrum of phonons, resulting the significantly decrease of thermal conductivity. In addition, this material design also leads to a very important improvement of the absolute Seeback coefficient value, which increases from about 50 μVK −1 to over 100 μVK -1 . As the result, the maximum ZT value is 0.86 at 523 K for a Ti doped sample, which is six times higher than the un-doped sample and is comparable to the best value for the CoSb3 based thin films. A flexible CoSb3 based thin film thermoelectric generator was also fabricated and shows that the response time of all the touch events is below 1 s.